Reconstructing Afghanistan. (International Monetary Fund, 2005)
This book, which reflects the IMF staff's work in Afghanistan from early 2002 through the first quarter of 2004, provides an overview of the institutional and economic achievements in Afghanistan in the post-Taliban period, that is, from late 2001 to early 2004. During this period, the staff focused on helping (often under difficult circumstances) the Afghan authorities quickly establish abasic framework for economic management and policies, including rebuilding key institutions. Reconstructing Afghanistan describes the strong economic recovery that took place during 2002 and 2003; traces the formulation and implementation of the government's budgetary policy; discusses the progress made in rebuilding fiscal institutions; and outlines the challenges and issues that the authorities faced in the area of monetary and exchange rate policy.